Benefit of Monitoring the Level of Blood Flecainide Acetate in an Elderly Patient with Ventricular Premature Contractions - Kaku, Takashi; Chiba, Kazuo; Ueda, Keiji; Nagashima, Juni-ich (Nihon Rōnen Igakkai zasshi, 1997)
A 67-year-old woman without organic heart disease had symptomatic ventricular premature contractions. Because class Ia, Ib and IV antiarrhythmic drugs did not prevent the premature contractions, the patient was treated with flecainide acetate at a dose of 50mg t.i.d. Adverse reactions were noted. After measurement of the blood drug level, the dose was reduced to 50mg b.i.d. The adverse reactions disappeared, and the arrhythmia was controled. Flecainide acetate has a relatively long blood elimination half-life and a narrow safety margin. When some antiarrhythmic drugs are used in elderly patients, blood drug level monitoring is useful in preventing adverse reactions and in designing appropriate therapy.